Effect of Supraphysiological Concentration of Serum Folate on Natural Killer Cell Activity in Healthy Subjects - Montoya-Kunsting, M (2012)
Background & aims: During the past few years, consumption of high amounts of folic acid and high serum levels of folate have been associated with cancer risk. Several mechanisms have been proposed to explain this association. One of them is that supraphysiological levels of folate may diminish natural killer (NK) cell cytotoxic activity and its action as an antitumoral barrier. To demonstrate this hypothesis, we studied the effect of serum folate levels on NK cell cytotoxic activity in healthy subjects. Methods: We recruited 227 healthy subjects of both sexes and measured serum folate levels and NK cell cytotoxic activity. Serum folate was adjusted for sex, age and body mass index to look for an association between its levels and cytotoxic activity of NK cell. Results: We found supraphysiological serum folate levels in 24% of studied subjects. NK cell cytotoxic activity was not associated with serum folate levels. There was no relation between NK cell activity and other variables such as age, sex and BMI. Conclusions: In this study, NK cell cytotoxic activity was not associated with serum folate levels. It is necessary to search for other hypothesis in order to explain the observed association between folic acid and cancer. © 2012 European Society for Clinical Nutrition and Metabolism.